Proposed Sales Increase Strategy (Marketing Mix 7P) Using the ANP Method for PT X Lavender Essential Oil Products - Nurul Alfiah; I Anna Tul Munikhah; Famila Dwi Winati (Jurnal Sistem Teknik Industri, 2023)
PT X is a company that produces certified organic essential oils derived from natural oils. PT X is sales not growing because competitors are very active, resulting in lower sales levels and company targets not being met. The purpose of this study is to use the Analytical Network Process (ANP) method to select the best criteria and alternatives in the 7P marketing mix and suggest the best marketing strategy. The criteria were selected based on ANP processing with Super Decisions software on the 7P marketing mix, namely product criteria with the highest weight of 0.28. The second ranking criterion is Physical Evidence with a weight value of 0.18 and the third criterion that has an effect is Price with a weight value of 0.16. The alternative selected from the order of these criteria is the efficacy of the product in accordance with the offered strategy which is carried out by emphasizing the efficacy of the product while always maintaining the ingredients or ingredients used. The second alternative is that the company name is well known, this alternative is carried out with a communication role strategy. The third alternative is the price offered in accordance with what is obtained by the customer, this strategy is carried out through the PT X marketing communication strategy which must be further deepened.